Study on Influence of Silicon Percentage on Flowability of Binary Aluminium-Silicon Alloy - Mohd Ichwan, Nasution, Ir.; Shamsul Baharin, Jamaludin, Assoc. Prof. Dr.; Che Mohd Ruzaidi, Ghazali, Assoc. Prof.; Faizul, Che Pa (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.